2000
DOI: 10.1063/1.1287333
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation formulas in molecular-dynamics simulations with the weak coupling heat bath

Abstract: The statistical mechanical ensemble associated with molecular-dynamics ͑MD͒ simulations with the weak coupling ͑WC͒ thermostat proposed by Berendsen et al. ͓J. Chem. Phys. 81, 3684 ͑1984͔͒ is analyzed. Using a generalized Liouville equation, an approximate equilibrium distribution function in the configurational space for the WC thermostat is obtained. From this distribution function, fluctuation formulas associated with the constant volume specific heat C v , pressure coefficient ␥ v , and isothermal compress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
170
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(174 citation statements)
references
References 19 publications
3
170
0
1
Order By: Relevance
“…10 We briefly describe the weak-coupling algorithm, focusing only on the constant-pressure case. In any Molecular Dynamics algorithm the integrator moves the velocities and positions in a time-step according to the equations of motion:…”
Section: The Reversible Weak-coupling Algorithmmentioning
confidence: 99%
“…10 We briefly describe the weak-coupling algorithm, focusing only on the constant-pressure case. In any Molecular Dynamics algorithm the integrator moves the velocities and positions in a time-step according to the equations of motion:…”
Section: The Reversible Weak-coupling Algorithmmentioning
confidence: 99%
“…An analogous technique is used in the Berendsen thermostat, for which it was shown that the resulting temperature distribution deviates from the theoretical distribution. 87 The second barostat technique in this work is the algorithm proposed by Martyna, Tuckerman, Tobias and Klein, the MTTK barostat. 39,40 The method can be seen as the natural extension of the Nosé-Hoover and Nosé-Hoover chain thermostat.…”
Section: Barostats Used To Control the Pressurementioning
confidence: 99%
“…The advantage of the Berendsen thermostat is that the system is weakly coupled to the external thermal bath [8], which leads to its slow relaxation to the reference temperature. However, the Berendsen thermostat has the shortcoming of not generating a canonical temperature distribution [9].…”
Section: Introductionmentioning
confidence: 99%